Evaluation of Nutritional Status and Yield Limiting Nutrients in Oil Palm Plantations of Cauvery Delta Zone of Tamil Nadu - K. Suresh and Ravi K. Mathur, Sanjib K. Behera, Arvind K. Shukla (Journal of the Indian Society of Soil Science, 2018)
Oil palm (Elaeis guineensis Jacq.) is grown in many countries, including India, to meet vegetable oilrequirement. Assessment of soil properties and leaf nutrient concentration in oil palm plantations is requiredfor effective nutrient management and higher crop yield. Therefore, the present study was carried out byanalyzing 104 soil samples and 52 leaf samples collected from oil palm plantations of Thanjavur district ofTamil Nadu, India. The soil properties like pH, electrical conductivity (EC), organic carbon (OC), availablenitrogen (N), phosphorus (P), potassium (K), exchangeable calcium (Ca) and magnesium (Mg) and availablesulphur (S) and boron (B) in 0-20 and 20-40 cm soil depth varied widely with CV values ranging from 7.44to 89.4%. Leaf nutrient concentration varied from 1.11 to 3.17, 0.05 to 0.18, 0.21 to 0.98, 1.24 to 2.23, 0.17to 0.86, 0.08 to 0.22% and 21.8 to 77.7 mg kg-1 for N, P, K, Ca, Mg, S and B, respectively. Diagnosis andrecommendation integrated system (DRIS) norms and indices were derived from different nutrientexpressions. The order of requirement of leaf nutrients was found to be K > P > N > Mg > B. Optimum leafnutrient range for N, P, K, Mg and B were estimated as 1.61 to 2.11%, 0.10 to 0.12%, 0.33 to 0.81%, 0.23to 0.73% and 30.6 to 54.8 mg kg-1, respectively, which could be used for guiding balanced application offertilizers. On the whole, 15, 31, 2, 8 and 10% of leaf samples had below optimum concentrations of N, P,K, Mg and B, respectively.